Dual anaerobic reactor model to study biofilm and microbiologically influenced corrosion interactions on carbon steel - Liam Jones; Maria Salta; Torben Lund Skovhus; Kathryn Thomas; Timothy Illson; Julian Wharton; Jeremy Webb (npj Materials Degradation)
Abstract Continual challenges due to microbial corrosion are faced by the maritime, offshore renewable and energy sectors. Understanding the biofilm and microbiologically influenced corrosion interaction is hindered by the lack of robust and reproducible physical models that reflect operating environments. A novel dual anaerobic biofilm reactor, using a complex microbial consortium sampled from marine littoral sediment, allowed the electrochemical performance of UNS G10180 carbon steel to be studied simultaneously in anaerobic abiotic and biotic artificial seawater. Critically, DNA extraction and 16S rRNA amplicon sequencing demonstrated the principal biofilm activity was due to electroactive bacteria, specifically sulfate-reducing and iron-reducing bacteria.